2015
DOI: 10.1039/c4dt03105a
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i) thiotetrazolates as thioredoxin reductase inhibitors and antiproliferative agents

Abstract: Gold(i) complexes with phosphane and thiotetrazolate ligands were prepared and investigated as a new type of bioactive gold metallodrugs. The complexes triggered very efficient inhibition of the enzyme thioredoxin reductase (TrxR), which is an important molecular target for gold species. Strong cytotoxic effects were observed in MDA-MB-231 breast adenocarcinoma and HT-29 colon carcinoma cells, and the complexes also caused strong effects in vincristine resistant Nalm-6 leukemia cells. Cellular uptake studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…As shown in Table , apart from 88 , other molecules displayed IC 50 values within the scope of 30 to 55 nM with more than 10‐fold selectivity for TrxR inhibition over GR. The cytotoxicity data for all compounds were determined (Table ) . Silva and co‐workers described the inhibition of TrxR for a gold (I) complex ( 91 , Figure B) and found 91 showed a better inhibition when compared to auranofin.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…As shown in Table , apart from 88 , other molecules displayed IC 50 values within the scope of 30 to 55 nM with more than 10‐fold selectivity for TrxR inhibition over GR. The cytotoxicity data for all compounds were determined (Table ) . Silva and co‐workers described the inhibition of TrxR for a gold (I) complex ( 91 , Figure B) and found 91 showed a better inhibition when compared to auranofin.…”
Section: Thioredoxin Reductase Inhibitorsmentioning
confidence: 99%
“…For example, Panda and Ghosh reported that a Au(I)‐NHC complex, [1‐benzyl‐3‐tbutylimidazole‐2‐ylidene] AuCl, exhibited excellent efficiency against the proliferation of HeLa cells (1.7% proliferation at [Au] 0 = 10 μM) . Ott and co‐workers discovered that Au(I)‐NHC‐based thiotetrazolates are effective thioredoxin reductase inhibitors and antiproliferative agents against breast and colon carcinoma cell lines . Likewise, Berners‐Price and Filipovska described a new approach to antitumor agents, where selective mitochondria targeting and thioredoxin reductase inhibition were achieved using Au(I)‐NHC complexes .…”
Section: Introductionmentioning
confidence: 99%
“…While gold and its salts have been used for hundreds to thousands of years, modern research has witnessed the development of more sophisticated bioactive complexes that contain several types of coordinated ligands (e.g. thiolates [7,8], phosphanes [9][10][11], porphyrines [12], dithiocarbamates Subsequently high level post-SCF calculations were used to determine bond dissociation energies of the ligand-gold bonds. This allows estimating the influence of ligand variations on the stability of their coordination bonds.…”
Section: Introductionmentioning
confidence: 99%